2021
DOI: 10.1111/nph.17290
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 methyltransferase SDG708 enhances drought tolerance by promoting abscisic acid biosynthesis in rice

Abstract: Chromatin modifications play important roles in plant adaptation to abiotic stresses, but the precise function of histone H3 lysine 36 (H3K36) methylation in drought tolerance remains poorly evaluated.Here, we report that SDG708, a specific H3K36 methyltransferase, functions as a positive regulator of drought tolerance in rice. SDG708 promoted abscisic acid (ABA) biosynthesis by directly targeting and activating the crucial ABA biosynthesis genes NINE-CIS-EPOXYCAROTENOID DIOXYGENASE 3 (OsNCED3) and NINE-CIS-EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…The CLUSTER PROFILER package for R software was used for GO analysis as previously described (Chen et al, 2021).…”
Section: Transcription and Transcriptome Analysesmentioning
confidence: 99%
“…The CLUSTER PROFILER package for R software was used for GO analysis as previously described (Chen et al, 2021).…”
Section: Transcription and Transcriptome Analysesmentioning
confidence: 99%
“…According to RNA-Seq analysis, SDG102 is necessary for the proper expression of numerous genes involved in diverse biological processes. In addition to flowering, ASH1 family proteins in rice and Arabidopsis such as SDG26 and SDG8 in Arabidopsis and SDG708 and SDG725 in rice also affect a variety of plant phenotypes reported in previous studies [28][29][30]33,40,43]. RNA-Seq analyses demonstrated that DEGs between the sdg102 mutants and the WT are distributed across functional categories such as hormone signal transduction, cell composition of the nucleosome and histone modification, carbohydrate metabolism, and response to stress.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to controlling the flowering time, SDG708 also acts as a positive regulator of drought tolerance. The overexpression of SDG708 increased the grain yield and drought tolerance under normal and drought stress conditions in rice [43]. The overexpression of rice SDG736 in A. thaliana, the closest rice homolog of Arabidopsis SDG4, resulted in early flowering.…”
Section: Introductionmentioning
confidence: 97%
“…OsSDG708 , encoding a putative H3K36 methyltransferase, positively regulates drought tolerance by directly targeting and activating the crucial ABA biosynthesis genes OsNCED3 and OsNCED5 in rice. Overexpression of OsSDG708 enhances the drought tolerance and increases the grain yield either, highlighting its potential role epigenetic regulation ( Chen et al, 2021b ). In dehydrated maize plants, higher active methylation (H3K36me3 and H3K4me3) and lower repressive methylation (H3K27me3) are deposited in the loci of antisense transcripts, indicating biogenesis of small RNAs might be regulated by histone methylation in drought response ( Xu et al, 2017 ).…”
Section: Two Dynamic Counterparts In Stress-responsive Gene Transcrip...mentioning
confidence: 99%
“…Later in another study, the authors found that FLD/SDG26/LD interacts with R-loop to slow both the transcription initiation and the elongation ( Xu et al, 2021 ). Since the ASH-group HKMTs are involved in drought tolerance ( Chen et al, 2021b ), the output when multiple epigenetic mechanisms are combinatorially involved needs to be reconsidered.…”
Section: Cross-talks Of Histone (De)methylation In Response To Osmoti...mentioning
confidence: 99%